2020
DOI: 10.26877/e-dimas.v11i4.5616
|View full text |Cite
|
Sign up to set email alerts
|

Cegah Stunting Sejak Dini dengan Makanan Bergizi untuk Ibu Hamil

Abstract: Stunting merupakan suatu kondisi yang sangat umum terjadi pada seorang anak dengan kekurangan gizi dikarenakan jumlah makronutrien dan mikronutrien tidak cukup memadai.Indonesia menempati peringkat kelima dunia untuk jumlah anak dengan kondisi stunting.Usaha dini yang dapat dilakukan untuk melakukan pencegahan stunting bisa dilakukan sejak masa kehamilan.Prinsipnya adalah meningkatkan asupan gizi ibu hamil dengan memastikan selama kehamilan ibu mengkonsumsi makanan yang bergizi dan berkualitas baik, oleh karen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…Prevention of stunting from an early age with nutritious food for pregnant women in the Wonocolo sub-district, Surabaya, it was found that from 40 respondents, most of the pregnant women had fulfilled their nutritional and nutritional needs for stunting prevention during pregnancy. 15 Malnutrition in pregnant women can cause poor conditions for babies in the womb, pregnant women who have not met balanced nutrition since the beginning of pregnancy have a risk of giving birth to Eni Hidayati / Pregnant Mother's Anxiety Level On Stunting Risk stunting babies or other disease disorders based on the research entitled balanced nutrition education for pregnant women in stunting prevention in the village. Karang Bayan, West Lombok Regency, it can be concluded that the more pregnant women who have fulfilled nutrition and nutrition since the beginning of pregnancy can prevent stunting and other baby abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of stunting from an early age with nutritious food for pregnant women in the Wonocolo sub-district, Surabaya, it was found that from 40 respondents, most of the pregnant women had fulfilled their nutritional and nutritional needs for stunting prevention during pregnancy. 15 Malnutrition in pregnant women can cause poor conditions for babies in the womb, pregnant women who have not met balanced nutrition since the beginning of pregnancy have a risk of giving birth to Eni Hidayati / Pregnant Mother's Anxiety Level On Stunting Risk stunting babies or other disease disorders based on the research entitled balanced nutrition education for pregnant women in stunting prevention in the village. Karang Bayan, West Lombok Regency, it can be concluded that the more pregnant women who have fulfilled nutrition and nutrition since the beginning of pregnancy can prevent stunting and other baby abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Sementara itu jika periode emas anak mengalami kekurangan gizi, maka tidak akan dapat diperbaiki di masa kehidupan berikutnya. Kekurangan gizi pada anak usia dini dapat mengganggu tumbuh kembang anak, kemampuan intelektual rendah, meningkatkan potensi kematian bayi dan anak, serta pada saat dewasa berpotensi terjadi gangguan metabolisme (Ningrum et al, 2020). Setiap kasus gangguan gizi akan mempengaruhi sistem kekebalan tubuh terhadap penyakit infeksi (Nadila, 2021).…”
Section: Pemahaman Tentang Pemenuhan Gizi Dan Sanitasi Dalam Keluargaunclassified
“…Selanjutnya pada anak usia dini perlu diberikan nutrisi yang cukup untuk melengkapi nutrisi kebutuhan harian. Kekurangan gizi pada anak usia dini dapat mengganggu tumbuh kembang anak, kemampuan intelektual rendah, meningkatkan kematian bayi dan anak, saat dewasa berpotensi terjadi gangguan metabolisme, sehingga gangguan pertumbuhan ini harus segera ditangani dengan tepat (Ningrum et al, 2020).…”
Section: Abstract (Sesuaikan Dengan Yang Sudah Diperbaikiunclassified